Software Product Line Reengineering: A Case Study on the Geographic Domain - Buccella, Agustina (2016)
The growing adoption of software product lines (SPL) represents perhaps a paradigm shift in software development aiming at improving cost, quality, time to market, and developer productivity. While the underlying concepts are straightforward enough building a family of related products or systems by planned and careful reuse of a base of generalized software development assets the problems can be in the details, as successful product line practice involves domain understanding, technology selection, and so forth. Today, there is an important increment on reporting experiences and lessons about SPL development by capturing aspects that have been gathered during daily practice. Following this line, in this paper we start from our experiences of developing a software product line on the Marine Ecology domain highlighting our reasons for reengineering a previous SPL. Then, we explain step-bystep reengineering activities in terms of motivation, solutions, and lessons learned, which summarize strengths and limitations of the applied practices. Differently from other cases, here we take advantage of using domain standards as well as open source implementations within the geographic domain.